Perspectives of ICU Physicians on Antibiotic Use in Critically Ill Patients: A Qualitative Study from a Developing Country: ICU Antibiotic Prescribing Practices - Khoso, Maheen; Arshad Taqi; Muhammad Aamir Alsabah; Faisal Imran; Naveed Latif (Journal of University College of Medicine and Dentistry, 2025)
Objective: To explore the experiences and perceptions of ICU consultants regarding antibiotic prescribing practices in critically ill patients within resource-limited healthcare settings. Methodology: This qualitative study, based on a phenomenological approach, was conducted between January 1 and December 30, 2023, at the National Hospital & Medical Center and DHA Medical Center, Lahore, Pakistan. Six ICU consultants with more than two years of post-fellowship experience were recruited through purposive sampling. Data were collected via face-to-face, semi-structured interviews, audio-recorded with consent. Thematic analysis was performed until data saturation was achieved. Results: Six major themes emerged. First, early initiation of antibiotics without confirmed diagnosis was reported as a routine and often necessary practice due to diagnostic uncertainty and delays in culture results. Second, barriers to antimicrobial stewardship (AMS) were noted, including the absence of formal AMS policies, poor interdepartmental coordination, and limited access to antibiograms—particularly in government hospitals. Third, factors influencing antibiotic selection included infection site, comorbidities, and family pressure, with variation between open and closed ICU models. Fourth, pharmaceutical incentives were largely deemed irrelevant in ICU prescribing due to the critical nature of decisions. Fifth, inflammatory markers like CRP and procalcitonin were valued for guiding antibiotic de-escalation, though high cost limited routine use. Finally, all participants expressed concern over the rise of antimicrobial resistance (AMR), highlighting the need for better microbiology infrastructure, public education, and regulated antibiotic access. Conclusion: ICU antibiotic prescribing is shaped by clinical urgency, systemic limitations, and contextual pressures. To mitigate the threat of AMR in low-resource settings, it is crucial to strengthen AMS programs, expand diagnostic capacity, and enforce locally adaptable prescribing protocols.